Are we paying-to-play? A quantitative assessment of Canadian open access research in ecology and evolution - Aaron B.A. Shafer (Canadian Science Publishing, 2021)
Open access (OA) allows for peer-reviewed research to be freely accessed and there has been a collective shift from both researchers and publishers towards more OA publishing. OA typically occurs either through article-processing charges (the gold road) or via self-archiving (the green road); the former can be expensive, while the latter has seen minimal uptake. The gold road of OA has led to predatory publishers and, to some, questionable publications. Here, I used publicly available grant information in Canada and combined this with individual publishing statistics to test a variety of factors and their influence on OA publishing. I showed that an individual's award amount, H-index, and gender did not influence the proportion of OA articles they published, but an individual's H-index scaled with the number of OA publications. Institute size influenced OA publishing patterns, with researchers at large universities (i.e., >20 000 full-time students) publishing proportionately more OA articles than medium and small institutes. I discuss the potential for this pattern to build on pre-existing systemic biases when it comes to funding and publishing.